(untitled) (Bangladesh Journal of Medical Education, 2024)
Introduction. In the recent global pandemic situation, Anatomy teaching-learning became mostly online-based. Increased use of social media for learning Anatomy is observed among medical students in Bangladesh. Although many students are constantly using social media for learning, there is a need for systematic studies about the outcome and future possibilities of social media in Anatomy education. Objectives. This study aimed to find the prospect of e-learning through social media as a complementary tool in Anatomy education in Bangladesh. Methods. The research was descriptive and cross-sectional. A self-administered questionnaire survey was conducted on 317 medical undergraduates, graduates, and postgraduates of Anatomy and other disciplines to analyze their experiences using social media for learning Anatomy and their perceptions, views, and suggestions regarding its use as a complementary tool. The data were analyzed using descriptive statistics. Results. Among the students, 55% were females, and 45% were males. About 95%, 84%, and 15% of the students used YouTube, Facebook, and Instagram to learn Anatomy. About 50% used YouTube, and 40% used Facebook daily. YouTube was found to be the most useful social media for learning Anatomy by 84% and Facebook by 12% of the students. These platforms became useful for the students in understanding difficult topics of Anatomy, developing interest, and preparing for examinations. The mean impact of social media on learning Anatomy was 3.603, indicating a positive impact. More than half of the students wanted to use social media as a complementary tool in the future. Different aspects of using Facebook and YouTube for learning Anatomy and suggestions for effective use were discussed. Conclusion. YouTube and Facebook are the two most popular social media for learning Anatomy as complementary tools among Bangladeshi medical students. There is ample scope for Anatomy educators to make useful video content on YouTube. BJME, Volume-15, Issue-01, January 2024: 36-48